(untitled) (Journal of Informatics Education and Research, 2025)
Employee well-being programs are critical for fostering a productive and committed workforce. Employee well-being initiatives are crucial for cultivating a productive and motivated staff, particularly in high-stress sectors such as private banking. Workers in this sector frequently endure extended working hours, elevated client expectations, and stringent performance standards, resulting in stress and job unhappiness. Well-being initiatives, such as mental health support, financial aid, flexible work arrangements, and career development programs, are essential for sustaining employee morale and organizational commitment. This study examines the effects of such initiatives on staff retention and satisfaction in private banks, utilizing empirical data from 122 respondents. Diverse statistical methodologies, such as factor analysis, correlation, regression, and hypothesis testing, are utilized to assess the efficacy of these activities. The findings reveal a robust positive correlation between well-being programs and organizational commitment, indicating that employees who receive organized support have increased job satisfaction and reduced turnover intentions. The report emphasizes that financial assistance and healthcare benefits substantially improve employee loyalty, whereas work-life balance programs foster long-term involvement. The findings highlight the imperative for private banks to invest in comprehensive well-being programs to enhance workforce stability and organizational performance. Through the implementation of comprehensive well-being initiatives, private banks can diminish employee turnover while fostering a more dedicated, engaged, and high-performing team.